Breeding for milk and beef in cattle - designing an overall strategy - Vilva, Veijo; Lindström, U. B. (Agricultural and Food Science, 1983)
A three-stage selection programme of dual purpose bulls was studied in order to assess the significance of the selection stages and the genetic gain to be expected. In accordance with previous studies the results showed that over 90 % of the economic gain comes from the milk traits. In addition the study showed that over 10 % of the gain is due to the increased feed conversion efficiency, mainly in milk production. The beef performance test of young bulls accounted for only 1—2 % of the total economic gain. Therefore the test stations setup for this purpose might be more efficiently utilised by concentrating on measurement of feed conversion. The study also indicated that direct selection for feed efficiency in milk production would give appreciably higher gain even if it were done on the basis of only 5 daughters/ bull. In practice this might be accomplished by measuring the feed consumption of a limited number of daughters per young bull, 4-5 months after calving for about one month or by collecting 200—300 individual mid-lactational feed consumption records for daughters of young bulls.